Analisis Pelaporan Sekolah Siaga Kependudukan melalui SIMONEV PENDUK di Jawa Timur - Niken Putri Hariyati (Yayasan Literasi Sains Indonesia, 2026)
The Population Awareness School Program is an initiative of the National Population and Family Planning Board (BKKBN) aimed at improving population literacy and awareness within schools. Its implementation and reporting are monitored through the Sistem Monitoring dan Evaluasi Pendidikan Kependudukan (SIMONEV PENDUK). This study analyzes the reporting performance of SSK and identifies challenges in monitoring and evaluation implementation through SIMONEV PENDUK in East Java Province. A descriptive qualitative approach was employed using secondary data from SIMONEV PENDUK accessed on December 13, 2025, supported by in-depth interviews and field observations conducted during the internship period. The findings reveal disparities in reporting performance across districts and municipalities, with some areas demonstrating high reporting rates while others show minimal or no data input. Key challenges include staff turnover, high administrative workload, uneven understanding of the SSK program among schools, and low awareness of reporting as part of the monitoring and evaluation process. Strengthening institutional capacity, establishing clear reporting targets, and implementing continuous monitoring and feedback mechanisms are necessary to optimize SIMONEV PENDUK and promote equitable SSK implementation in East Java.